The Mainstreaming of Pakerti Adiluhung for Islamic Education Providers: Lessons Learned from Madrasah Ibtidaiyah Terpadu Arroihan Malang - Mukaffa, Zumrotul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This article presents an analysis of the significance of ensuring equal access to education for children with special needs in alignment with Islamic values. It is argued that verses such as Surah Abasa, verses 1-4, and Surah al-Nur, verse 61, support the concept of inclusive education. The observation method was employed in the analysis of the data, and it was concluded that Pakerti Adiluhung (noble values) in inclusive education at MIT Ar-Roihan Lawang Malang play an important role in living God’s existence, being responsible for humanitarian duties and being consistent in carrying out professional duties. Such values constitute the bedrock upon which every educational provider, particularly teachers, must be built. The implementation of these values at MIT Ar-Roihan has resulted in notable outcomes, including enhanced student achievement, community appreciation, and recognition from authorities. The portrait of MIT Ar-Roihan provides important inspiration that the success of educators in implementing the three noble principles has a tangible impact on the achievements of the madrasah. In addition to the growing appreciation of the community and the state through the Ministry of Religious Affairs, the madrasa has also successfully guided students to achieve excellence in various fields at local, regional, national and international levels.